The Savvy Survey #4: Details in the Design - Glenn D. Israel; Jessica L. Gouldthorpe (EDIS, 2013)
As part of the Savvy Survey Series, this publication provides an overview of important facets of the survey process. Topics covered include modes for collecting responses, strategies for contacting clients and personalizing contacts, and tips for using incentives. The ability of a survey to gather accurate and useful information for assessing program needs or evaluating program outcomes is greatly influenced by the survey’s design. Careful attention to detail is essential. This 4-page fact sheet was written by Glenn D. Israel and Jessica L. Gouldthorpe, and published by the UF Department of Agricultural Education and Communication, October 2013. http://edis.ifas.ufl.edu/pd064